2015
DOI: 10.2337/dc14-2351
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Risk Estimates of Three HbA1c Variables for Myocardial Infarction in 101,799 Patients Following Diagnosis of Type 2 Diabetes

Abstract: OBJECTIVEThis study evaluated the risk of myocardial infarction (MI) by impaired glycemic control in a contemporary large cohort of patients with type 2 diabetes followed from diagnosis. RESEARCH DESIGN AND METHODSPatients with type 2 diabetes diagnosed between 1995 and 2011 were retrieved from the Clinical Practice Research Datalink in the U.K., and followed from diagnosis until event of MI or end of study in 2013. Two subcohorts were defined: an early cohort with those diagnosed from 1997 to 2004 and a recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
(21 reference statements)
3
10
0
Order By: Relevance
“…Nonetheless, this is an essential point from our findings since the HRs described by 1% higher HbA 1c differ greatly depending on the HbA 1c metric used. It is noteworthy that in accordance with our recent analysis of HbA 1c in relation to MI (15), there was a J-shaped pattern for the latest HbA 1c variable. Although this finding is repeated here for another CV complication and it could be inferred that very tight glycaemic control, for example, HbA 1c close to normal levels may be harmful, it should be interpreted with caution since patients with HbA 1c <6% (42 mmol/ mol) have a glycaemic control lower than general targets.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Nonetheless, this is an essential point from our findings since the HRs described by 1% higher HbA 1c differ greatly depending on the HbA 1c metric used. It is noteworthy that in accordance with our recent analysis of HbA 1c in relation to MI (15), there was a J-shaped pattern for the latest HbA 1c variable. Although this finding is repeated here for another CV complication and it could be inferred that very tight glycaemic control, for example, HbA 1c close to normal levels may be harmful, it should be interpreted with caution since patients with HbA 1c <6% (42 mmol/ mol) have a glycaemic control lower than general targets.…”
Section: Discussionsupporting
confidence: 90%
“…14 Recently, we found that the estimates of glycaemic control in relation to myocardial infarction varied over time with less strong associations during more recent time periods. 15 The most commonly used measure of glycaemia is haemoglobin A 1c (HbA 1c ). 16 However, a deeper understanding of the statistical application of repeated measures of HbA 1c is needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the large clinical randomized controlled trials have failed to show a clear beneficial effect of early intensive glycemic control on cardiovascular events in type 2 diabetes (5), long-term follow-up studies from the UK Prospective Diabetes Study (UKPDS) (8) and Veterans study (9) have suggested a beneficial cardiovascular effect, termed "metabolic memory" or "legacy effect." (10) In observational research, most studies, but not all, suggest that having a low glycemic level measured at some point of time is associated with fewer cardiovascular events and mortality in type 2 diabetes (11)(12)(13)(14)(15)(16)(17)(18). Some studies found a linear relationship between successively lower glycemic levels and fewer cardiovascular events (11,12,18), whereas others reported a J-or U-shaped curve (14)(15)(16).…”
mentioning
confidence: 99%
“…(10) In observational research, most studies, but not all, suggest that having a low glycemic level measured at some point of time is associated with fewer cardiovascular events and mortality in type 2 diabetes (11)(12)(13)(14)(15)(16)(17)(18). Some studies found a linear relationship between successively lower glycemic levels and fewer cardiovascular events (11,12,18), whereas others reported a J-or U-shaped curve (14)(15)(16). Comparison of these studies is hampered by inclusion of case patients with prevalent diabetes with different time of diabetes duration and by different ways of measuring glycemic control.…”
mentioning
confidence: 99%